Bioethanol Production from Sugar Cane Molasses - Wan Muhd Farid, Wan Hamat (2012)
The use of biofuels as an alternative to fossil fuels has expanded in the last few decades. In recent years, growing attention has been devoted to the conversion of biomass into ethanol fuel, which is considered as the cleanest liquid fuel alternative to fossil fuels. Production of ethanol (bioethanol) from biomass is one way to reduce both consumption of crude oil and environmental pollution. An analysis of the current situation and perspective on biomass-to-ethanol is provided in this study. Various conversion pathways are compared from technical, economic, and environmental points of view. This study also deals mainly with the yield of ethanol from molasses with respect to the dilution ratio and the amount of yeast used for fermentation keeping the temperature and fermentation duration constant. Sugarcane molasses is be used for the feedstock in this study. Sugarcane molasses is a viscous by-product of the processing of sugar cane into sugar. Therefore, sugarcane molasses such as agricultural wastes are attractive feedstock for bioethanol production. Agricultural wastes are cost effective, renewable and abundant. In this study, the yeast used is Saccharomyces cerevisiae. Saccharomyces cerevisiae is the cheapest strain available for the conversion of biomass substrate. As conclusion, it was observed that with an increase in yeast quantity the ethanol yield increases reaching optimum yeast quantity then the ethanol yield start to decrease and the optimum ratio for molasses and water was 1:2. It can be concluded that the yield of ethanol is greatly dependent on the quantity of fermentable sugars present in the biomass.